Spousal Support in Quebec: Resisting the Spousal Support Advisory Guidelines / Pensiones alimenticias para cónyuges en Quebec: La resistencia a las Spousal Support Advisory Guidelines - Lazare, Jodi (Les Cahiers de droit, 2018)
Since 2005, the Spousal Support Advisory Guidelines have become an essential part of the practice of family law throughout Canada. Aimed at structuring discretionary spousal support determinations under the Divorce Act and increasing the fairness of awards, the Advisory Guidelines have been embraced by appellate courts across jurisdictions. Quebec is the exception to that trend. Despite that marriage and divorce fall under federal jurisdiction, Quebec courts resist the application of these non-binding rules, written by two family law scholars. This article responds to Quebec’s resistance to the Advisory Guidelines and suggests that concerns about them may be misplaced. By reviewing the history of Quebec’s legislative approach to married spouses, it suggests that antipathy toward the Advisory Guidelines, based on their failure to reflect Quebec matrimonial law, is misguided. Rather, judicial approaches in Quebec based on autonomy and economic independence fail to reflect the reality of both the provincial and federal legislative landscapes respecting marriage and divorce.